PEMAHAMAN MAHASISWA PENDIDIKAN BIOLOGI FKIP UNIVERSITAS RIAU TENTANG KURIKULUM 2013 - Suryani, Neneng Suryani Neneng; Syafi’i, Wan Syafi’i Wan; ', Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research has been to know understanding student of biology education on the curriculum 2013 faculty of teacher training and education university of Riau. This typenof research is a descriptive study. The sample was students of biology education faculty of teacher training and education university of Riau, sixth semester written 98 peoples. The understanding indikators of competency standards, content standards, process standards and assesment standards. Data collection techniques using a written test 60 question that carried out by collecting the sixth semester students in a room then researchers give time for 90 minutes to fill in the comprehension test. After completing the test comprehension, directly handed over to investigators. This data is used as research data for analysis and interpretation done. From the results obtained can be seen in the percentage of students understanding of competency standards obtained 65,8% with sufficient criteria. A standard indicator of the content of 68,9% was obtained with sufficient criteria. The standard indicators obtained 70,0% with good criteria and indicators of appraisal standards was obtained 73,4% with good criteria. It can be concluded that the understanding gained 69,5% with sufficient criteria.Keyword : Understanding, Student of Biology Education, Curriculum 2013